Bioproducts against food-borne pathogenic bacteria - Benitez, Lisianne Brittes; dos Santos, Ariana Pereira; Muller, Ana Paula; de Souza, Thamires Klein (Comunicata Scientiae, 2018)
Advances in biotechnology research show the rising generation of a variety of products derived from microbial, plants and animal sources. These products are known as “bioproducts” or “natural products”. The preservation of the microbiological quality of foods without the use of chemical preservatives has become a challenge stimulating new researches on conservation alternatives. The aims of this study were the assessment of the the antibacterial activity of several bioactive compounds: essential oils of orange, lavender, green and red mandarins; ethanol extract of oregano and protein hydrolyzed from shrimp shell against Escherichia coli and Staphylococcus aureus isolated from foods, and the comparison between two different methods used in the screening of natural products with potential antibacterial activity. The antibacterial activities of the natural compounds were determined using agar diffusions tests and bioautography methods. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined for the essential oils of orange and lavender, and the ethanolic oregano extract. The essential oils of orange and lavender and the ethanolic oregano extract showed antimicrobial activity against all bacteria tested in the study. The agar disk diffusion and the bioautographic methods showed no significant difference in the evaluation of the biological activity of natural products.